PENGARUH PERSONAL SELLING DAN WORD OF MOUTH TERHADAP PENGAMBILAN KEPUTUSAN MAHASISWA MEMILIH KULIAH DI STIE EKA PRASETYA - Ihdina Gustina; Viviani (Jurnal Manajemen Bisnis Eka Prasetya, 2019)
ABSTRACT This study aims to determine the effect of Personal Selling and Word Of Mouth on Student’s Decisions to Study In STIE Eka Prasetya. The research methodology used is descriptive quantitative method. The type of data used in this study is quantitative data, which is obtained in the form numbers. Source of data in the form of primary data and secondary data. Primary data obtained from questionnaires, secondary data obtained from companies, journals and books relating to Personal Selling and Word Of Mouth and Study Decisions. The population and sample in this study amounted to 268 customers Data analysis using multiple linear regression analysis methods. The results of the analysis give an equation of the Purchase Decision = 11,034+ 0,544 Personal Selling +0,377 Word Of Mouth + e. The results of the analysis show that the Personal Selling has a positive and significant effect on the decision to study in STIE Eka Prasetya based on the partial test results, namely the tcount 7,303 > ttable 1,650 and the significance value of 0.000 <0.05. The results showed that Word Of Mouth had a positive and significant effect on the decision to study in STIE Eka Prasetya based on the results of partial tests, namely tcount 7,592 > ttable 1,650 and significant values ​​of 0,000 <0,05. The results showed that Personal Selling and Word Of Mouth had a positive and significant effect on the decision to study in STIE Eka Prasetya based on simultaneous test results, namely Fcount 129,474 > Ftable 3.17 with a significant value of 0.000 <0.05. The results of this study are supported by the value of R Square of 1,886 meaning Personal Selling and Wod Of Mouth can explain Study Decision of 49,4% and the remaining 50,6% is influenced by other variables outside of this study such as price, sales promotion and service quality.